Notes on some new Diademodon specimens in the collection of the Bernard Price Institute - Brink, A. S. (Bernard Price Institute for Palaeontological Research, 1963)
Seven Diademodon specimens are dealt with and all are reasonably adequately figured. These comprise a large D. mastacus specimen already featured in publication; a complete skull of D. grossarthi; an interesting snout of D.haunhtoni; and four immature D.browni specimens of various ages and sizes. The latter form part of about eight similar individuals found in an area some two yards square and could be the litter of a single Diademodon family. Attention is focused on the snouts and the peculiar nature of the external nares.
Main article
Keywords: Diamdemodon; Bernard Price Institute